2021
DOI: 10.1073/pnas.2015764118
|View full text |Cite
|
Sign up to set email alerts
|

Human arrival and landscape dynamics in the northern Bahamas

Abstract: The first Caribbean settlers were Amerindians from South America. Great Abaco and Grand Bahama, the final islands colonized in the northernmost Bahamas, were inhabited by the Lucayans when Europeans arrived. The timing of Lucayan arrival in the northern Bahamas has been uncertain because direct archaeological evidence is limited. We document Lucayan arrival on Great Abaco Island through a detailed record of vegetation, fire, and landscape dynamics based on proxy data from Blackwood Sinkhole. From about 3,000 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
2
12
0
1
Order By: Relevance
“…Continental and maritime sources contributed BC to the sediment cores, especially NC, which was enriched in δ 13 C ratio representing C3 plant and fossil fuels (Bush et al, 2007), while the OC fraction indicated a marine origin. Meanwhile, the average BC δ 13 C values at FS sites seemingly emphasized marine sources but could reflect a combination of C 3 plants (Fall et al, 2021) and fossil derived (i.e., oil) marine sources (Wozniak et al, 2012). Wagner et al (2019) suggested that the δ 13 C signatures can undergo changes during photolytic exposures and other processes including sorption/desorption during delivery to the bottom sediment, though particulate BC is considered to be recalcitrant.…”
Section: Origin Of Black Carbonmentioning
confidence: 99%
“…Continental and maritime sources contributed BC to the sediment cores, especially NC, which was enriched in δ 13 C ratio representing C3 plant and fossil fuels (Bush et al, 2007), while the OC fraction indicated a marine origin. Meanwhile, the average BC δ 13 C values at FS sites seemingly emphasized marine sources but could reflect a combination of C 3 plants (Fall et al, 2021) and fossil derived (i.e., oil) marine sources (Wozniak et al, 2012). Wagner et al (2019) suggested that the δ 13 C signatures can undergo changes during photolytic exposures and other processes including sorption/desorption during delivery to the bottom sediment, though particulate BC is considered to be recalcitrant.…”
Section: Origin Of Black Carbonmentioning
confidence: 99%
“…Our findings indicate a rapid migration of persons into and within the Bahamian archipelago (Fall et al, 2021;Keegan, 2010), most likely from Hispaniola. This is evident in the distribution of mtDNA haplogroups, which illustrates that the oldest haplogroup, B2, is found primarily in the northernmost islands.…”
Section: Y-chromosome Diversitymentioning
confidence: 70%
“…Haplogroup B2 is rare (>2%) across ancient Caribbean samples and modern Caribbean peoples in contrast to A2 and C1 (>20% in some Greater Antilles) (Paulino‐Ramirez et al, 2019; Vilar et al, 2014). The dominance and widespread geography of B2 lineages in the Northwest Bahamas shows that population expansion across the entire archipelago occurred rapidly, and that there was not a single propagule but waves of migration from a coherent homeland over a period of perhaps a century (see Fall et al, 2021). Genetic relationships with Hispaniola, and to a lesser degree Puerto Rico, also demonstrate that the Bahamian archipelago likely had stronger influences from Hispaniola than from any other place.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was sufficient genetic substructure to distinguish a subclade comprised of individuals from The Bahamas and Ceramic Age Cuba whose homeland is traced to Hispaniola. All of the islands were settled at a rapid rate, possibly in less than a century (Fall et al, 2021). A 3D morphometric study, which included the three complete crania (B1, B3, & B4) from this study and others from The Bahamas, revealed that the facial morphology of the Lucayans clustered with individuals from Hispaniola and Jamaica and were significantly different from Puerto Rico and Archaic Age Cuba (Ross et al, 2020).…”
Section: Discussionmentioning
confidence: 99%